A Comparative Study of Moral Values Education in Public and Religion-Based Kindergartens in Yogyakarta - Cholimah, Nur; Tjiptasari, Fitriana; Asih, Sri; Hanum, Aliyah Latifah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
Integrating moral values into early childhood education remains a critical issue for educators and policymakers worldwide. This study explores the implementation of moral values education in public and religion-based kindergartens in Yogyakarta. Using a descriptive quantitative approach, data were gathered through surveys and interviews from a sample of 20 kindergartens, ten public and ten religion-based, across five districts. The research focuses on how core moral values such as politeness, honesty, responsibility, and cooperation are taught and incorporated into daily learning activities. Results indicate that both public and religion-based kindergartens emphasize similar core values, though religion-based institutions place added importance on religious practices like daily prayers. Storytelling is more frequently employed in religion-based kindergartens to teach moral values. In contrast, public kindergartens utilize more diverse strategies, including group activities and discussions. Teachers in public kindergartens often encounter challenges with inconsistency between home and school environments regarding moral education, while those in religion-based kindergartens report difficulties managing children during religious activities. The findings underscore the need for improved home-school collaboration in public kindergartens to ensure consistency in moral education. In contrast, religion-based kindergartens could benefit from adopting more interactive and reflective teaching methods to foster critical thinking in children. Teacher training programs should focus on equipping educators with culturally sensitive strategies for moral education. Although this study offers valuable insights, its findings are geographically limited to Yogyakarta, and future research should broaden the scope to include different regions and assess long-term impacts on children’s moral development.